Personal Values Profile of Secondary School Students: A comparative study on Social Class Backgrounds. - Shahidul, S.M.; Zehadul Karim, A.H.M.; Mohammad Abu Suffiun, Samrat (IJRDO - Journal of Social Science and Humanities Research, 2016)
The core objective of this study is to explore whether personal values priority of students vary according to their social class backgrounds and if so to describe the underlying causes to that discrepancies. This study is based on a survey carried out in one of the town zone of the subdistrict in Bangladesh through interviews with questionnaires. We received responses from 335 students in the age range 12-16 years. Data have been analyzed with the help of Mean, Standard deviation (S.D) and t-test to study different values of students. The study highlights that students with lower class family background have more religious value compare to the students with higher class family background. Conversely, students with higher class family background have more democratic and power values compare to the students with lower class background. Furthermore, though some values vary in class backgrounds of students but the differences are not statistically significant.